1995
DOI: 10.1172/jci117849
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines from activated T cells induce normal endothelial cells to acquire the phenotypic and functional features of AIDS-Kaposi's sarcoma spindle cells.

Abstract: Kaposi's sarcoma (KS) is a proliferative disease of vascular origin particularly frequent in HIV-1-infected homosexual men (AIDS-KS) and characterized by proliferating spindleshaped cells, angiogenesis, and inflammatory cell infiltration. Previous work has suggested that KS spindle cells are of endothelial cell origin and that chronic immune activation via the release of inflammatory cytokines may cooperate with basic fibroblast growth factor (bFGF) and the HIV-1 Tat protein in the induction and progression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 62 publications
8
93
0
Order By: Relevance
“…However, the concentration of oncostatin M in focal lesions that contain activated T cells or macrophages could be much higher than circulating levels. For example, conditioned medium from HTLV-II infected T cells contains 20 to 45 nM oncostatin M (15). Thus the local concentrations of macrophage-like cells in aneurysmal tissue that stained heavily for oncostatin M, or the localized production of oncostatin M in the lesions of AIDS-associated Kaposi's sarcoma (7,39) may allow the low affinity oncostatin M receptor to participate in endothelial cell activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the concentration of oncostatin M in focal lesions that contain activated T cells or macrophages could be much higher than circulating levels. For example, conditioned medium from HTLV-II infected T cells contains 20 to 45 nM oncostatin M (15). Thus the local concentrations of macrophage-like cells in aneurysmal tissue that stained heavily for oncostatin M, or the localized production of oncostatin M in the lesions of AIDS-associated Kaposi's sarcoma (7,39) may allow the low affinity oncostatin M receptor to participate in endothelial cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, endothelial cells respond to oncostatin M with activation of MAP kinase activity (11), IL-6 secretion (9), and delayed, but prolonged, P-selectin synthesis (12). Third, oncostatin M is the major autocrine growth factor for Kaposi's sarcoma cells (13), and these spindle-shaped cells are thought to be of endothelial cell origin (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the most relevant targets for Tat is the vascular system, where it activates a pro-inflammatory and angiogenic program. Tat can up-regulate the expression of EC adhesion molecules [69,70] and induces EC to proliferate, release proteolytic enzymes [71][72][73][74][75][76][77][78][79]. These effects are potentiated by cell priming with inflammatory cytokines [71,72,80].…”
Section: Indirect Effect Of Hiv-1 On Ec Behavior: the Role Of Tatmentioning
confidence: 99%
“…12 The physiopathological significance of the proliferative effect of OSM on vascular cells is strengthened by the fact that OSM is 1 of the most potent stimulators of Kaposi sarcoma cell growth, 41,42 since some authors have demonstrated that Kaposi sarcoma spindle cells can be derived from endothelial cells 43 activated by proinflammatory cytokines. 44 The physiological significance of the angiogenic property of LIF can be considered in embryonic genesis, since Gendron et al 45 have demonstrated that LIF, in combination with bFGF, contributes to the induction and support of embryonic vasculogenesis in vitro and in vivo after blastocyte injection. However, compared with OSM, LIF does not seem to be involved in vessel wall injury leading to atherosclerotic development but could have a protective effect in atherosclerosis as shown by Moran et al 46 in hyperlipidemic rabbits.…”
Section: Vasse Et Almentioning
confidence: 99%